The Trilingual Literature of Polish Jews from Different Perspectives : In Memory of I.L. Peretz. - Molisak, Alina (Cambridge Scholars Publishing, 2017)
Are the literary works of Polish Jews one unified literature in three languages: Yiddish, Hebrew and Polish, or is the literal corpus of each of these languages a separated literary and cultural phenomenon? Twenty-seven scholars from Europe, the United States, and Israel explore different aspects of the multilingual literature of Eastern European Jews, with a particular focus on the trilingual literature of Polish Jews until World War II. The work of the great Yiddish and Hebrew writer Isaac Leib Peretz (1852-1915) represents the center of the book, though it does not concentrate solely on Pere.